2019
DOI: 10.1108/ijoem-07-2018-0400
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic determinants of sovereign bond market development in African emerging economies

Abstract: Purpose Despite being a viable source of funds, African sovereign bond markets are relatively underexplored. The empirical literature fails to consider the impact of exclusively macroeconomic factors and the volatile contexts in which African markets operate. The purpose of this paper is to fill the vacuum by proposing a context-sensitive theoretical framework. The study targets, specifically, macroeconomic factors and assesses the extent to which they affect bond market development. Design/methodology/appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
3
6
0
Order By: Relevance
“…The positive sign of the coefficient assigned to GDP per capita suggests that Saudi economy has attained a certain degree of development allowing it to have larger government bond market. These results seem to be in line with the most studies’ findings on the determinants of BMD [ 62 , 11 , 21 , 51 , 52 ]…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The positive sign of the coefficient assigned to GDP per capita suggests that Saudi economy has attained a certain degree of development allowing it to have larger government bond market. These results seem to be in line with the most studies’ findings on the determinants of BMD [ 62 , 11 , 21 , 51 , 52 ]…”
Section: Resultssupporting
confidence: 92%
“…Notwithstanding the growing body of literature that emerged examining the determinants of BMD, this paragraph is not intended to provide an exhaustive review of the theoretical and/or empirical related literature. In this regard, the main studies examining the factors affecting the size of LCBMs in different regions are: Claessens et al [ 43 ], Eichengreen and Luengnaruemitchai [ 11 , 44 ], Luengnaruemitchai and Ong [ 45 ], Eichengreen et al [ 46 ], Borensztein et al [ 47 ], Burger and Warnock [ 48 ], Adelegan and Radzewicz-Bak [ 49 ], Garcia-Kilroy and Silva [ 50 ], Bhattacharyay [ 15 ], Felman et al [ 18 ], Gray et al [ 19 ], Burger et al [ 16 ], Ayala et al [ 13 ], Khalid and Rajaguru [ 51 ], and Ahwireng-Obeng and Ahwireng-Obeng [ 52 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These results underscore the importance of macroeconomic variables in explaining determinants of government bond liquidity. The result is similar to Ang & Piazzesi (2003) who found that macroeconomic factors contribute to 85% of the variations as well as Ahwireng-Obeng (2016) in the case of 26 African countries. The result is also similar with the case of corporate bonds, as documented in Nigerian bond market (Nkwede, Uguru, & Nkwegu, 2016).…”
Section: Resultssupporting
confidence: 87%
“…The results of this study are also in line with research conducted by 39 , 40 , 41 , and 42 which argued that inflation had no significant effect on bond yields. Viewed from the direction of the coefficients, the results of this study are in line with 43 and 44 which state that inflation has a negative impact on the development of the state bond market. He further explained that the insignificance of the inflation variable reflects the development of a less developed financial market in a country.…”
Section: Inflation On Sukuk Returnsupporting
confidence: 86%